2008
DOI: 10.5483/bmbrep.2008.41.9.645
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis nucleoside diphosphate kinase-2 as a plant GTPase activating protein

Abstract: Nucleoside diphosphate kinase (NDPK) is involved in multiple signaling pathways in mammalian systems, including G-protein signaling. Arabidopsis NDPK2, like its mammalian counterparts, is multifunctional despite its initial discovery phytochrome-interacting protein. This similarity raises the possibility that NDPK2 may play a role in G-protein signaling in plants. In the present study, we explore the potential relationship between NDPK2 and the small G proteins, Pra2 and Pra3, as well as the heterotrimeric G p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 45 publications
2
8
0
Order By: Relevance
“…Arabidopsis NDPK2, like its mammalian counterparts, is multifunctional despite its initial discovery phytochrome-interacting protein. Resent reports suggest that NDPK2 acts as a GTPase-activating protein for small G proteins in plants and they propose that NDPK2 might be a missing link between the phytochrome mediated light signaling and G protein-mediated signaling [36]. In this study, NDPK was upregulated by SCMV infection, suggesting that NDPK was also involved in plant-virus interaction.…”
Section: Resultssupporting
confidence: 52%
“…Arabidopsis NDPK2, like its mammalian counterparts, is multifunctional despite its initial discovery phytochrome-interacting protein. Resent reports suggest that NDPK2 acts as a GTPase-activating protein for small G proteins in plants and they propose that NDPK2 might be a missing link between the phytochrome mediated light signaling and G protein-mediated signaling [36]. In this study, NDPK was upregulated by SCMV infection, suggesting that NDPK was also involved in plant-virus interaction.…”
Section: Resultssupporting
confidence: 52%
“…By this reaction, NDPK controls the level of GTP, which is, for example, required for the conversion of inactive GDP-bound GTPases to the active GTP-bound form. NDPK2, another isoform of NDPK in Arabidopsis, was shown to bind and stimulate the GTPase activity of small G proteins and serve as a signal transducer in phytochrome signaling (Choi et al, 1999;Shen et al, 2008). Interestingly, it was previously shown that NDPK activity is required for dynamin-dependent endocytosis in Drosophila (Krishnan et al, 2001) and that the level of GTP-bound dynamin proteins controls the level of endocytosis (Sever et al, 2000).…”
Section: Two Kinases With Putative Regulatory Functionsmentioning
confidence: 99%
“…Similar to NME proteins in mammals, NDPK isoforms in plants also perform diverse important roles [49]. NDPK2 from Arabidopsis thaliana was proposed to function as a GAP for small GTPases Pra2 (RabA3) and Pra3 (RabA4), which belong to the Rab family [50]. Active Rab5 and Rab7 play crucial roles in promoting the interaction of vesicles with lysosomes [51,52].…”
Section: Gap Activity Of Nme Proteinsmentioning
confidence: 99%